The Essential History of a Patient with Pearson Marrow, a Case Report - Malek, Fatemeh; Tavana, Parastoo; Mohkam, Masumeh (Journal of Pediatric Nephrology, 2020)
Pearson syndrome is a rare mitochondrial disorder confirmed by mt-DNA deletion which typically occurs in the first two years of life. That is to say children are at high fatal risk, most infants are marked with some common features especially anemia and pancreatitis, which results in death in early childhood. A 6-month-old Iranian female infant was presented with macrocytic anemia, required packed red blood cell transfusions. She also was affected by exocrine pancreatic dysfunction, in which she underwent Creon treatment. By first year of age she had experienced some severe metabolic crises intermittently. After hospitalized for some months she was expired unfortunately. In conclusion, Pearson syndrome, as a rare disease affects many organs, such as liver, kidney, pancreas, bone marrow, which led to anemia, failure to thrive, and multi organ failure. In such cases, a physician must consider and evaluate all possible damages, especially anemia and pancreatitis. We present a case of Pearson syndrome with anemia Keywords: Mitochondrial disorders; Pearson syndrome; Pancreatitis; Acidosis; Infants.